2019
DOI: 10.1177/2324709619879631
|View full text |Cite
|
Sign up to set email alerts
|

A Single Liver Metastasis From Adenoid Cystic Carcinoma of the Parotid Gland: Case Report

Abstract: Adenoid cystic carcinoma is an uncommon malignant neoplasm of the salivary gland. Liver metastasis from salivary gland cancer is a rare situation. In this article, we report the case of a 29-year-old woman treated 5 years previously for adenoid cystic carcinoma of the parotid gland by surgery and radiotherapy, who presented for a large hypervascularized hepatic metastasis of 20 cm. After 3-cycle chemotherapy stability, hepatic surgery was successfully performed. The patient maintained disease-free period of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…2,5-7 ACC liver metastases initially have slow growth and become symptomatic when the hepatic parenchyma is compromised. In a few studies, 2,6,7 it has been reported that ACC nodules were palpable or caused hepatomegaly. In the present case, the patient was asymptomatic and the diagnosis was made during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,5-7 ACC liver metastases initially have slow growth and become symptomatic when the hepatic parenchyma is compromised. In a few studies, 2,6,7 it has been reported that ACC nodules were palpable or caused hepatomegaly. In the present case, the patient was asymptomatic and the diagnosis was made during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, surgery is the most curative treatment for distant metastasis of ACC. [5][6][7][8][9][10] Zemni et al 7 described treatment with chemoembolization for a large ACC liver metastasis but when this approach failed they moved to surgical treatment. 7 In another report, Balducci et al 8 performed a two-stage hepatectomy for four large ACC metastases of the right liver with a previous right portal vein embolization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten patients were found to have lung metastases before liver metastases. The other 13 case reports in PubMed were reviewed in Table 2 (5,8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Clinical Characteristics Of Liver Metastasesmentioning
confidence: 99%